Modelagem geológica e geofísica 2,5-D de bacias paleozóicas da região amazônica:caso da bacia do solimões - NEVES, Herbert Duarte (2019)
The diabase sill has a great relevance over the maturation process of the organic material in whole Paleozoic Brazilian basin, however, it’s making hard the seismic exploration because the sill disturb the seismic signal, with multiple reflections and spherical divergence. The modeling of these complex geologic structures provides us better understand of then, and thus support the development of new techniques to reduce the exploration risks for oil industry. In this research present the results of 2,5- D modeling of complex geologic structures, where they’re build up the geologic (structural and statigraphic) and geophysical (velocity) models. These results were obtained by using the GOCAD (Geological Object Computer Aided Design) software, applied over a set of processed synthetic data.